2010
DOI: 10.1002/anie.201003292
|View full text |Cite
|
Sign up to set email alerts
|

Inside Cover: Controlled Reducibility of a Metal–Organic Framework with Coordinatively Unsaturated Sites for Preferential Gas Sorption (Angew. Chem. Int. Ed. 34/2010)

Abstract: The controlled reducibility of coordinatively unsaturated iron sites in MIL‐100(Fe), [Fe3O(H2O)2F0.81(OH)0.19{C6H3(CO2)3}2]⋅14.5 H2O, is described by J.‐S. Chang and co‐workers in their Communication on Thermal activation of MIL‐100(Fe) generates coordinatively unsaturated sites with mixed‐valence FeII/FeIII, leading to preferential sorption selectivity towards unsaturated gas molecules such as propylene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…4), a phenomenon most oen observed in equilibrium-based olen/paraffin separations. 28 Together, these data provide strong evidence that it is quite important in POP-based gas separation to have a proper size matching of the adsorbent pores to that of the adsorbate molecules. For the metallated materials reported herein, this size-matching mechanism can become important aer the rst olen binds to the metal center and reduces the accessibility of the metallated pores for subsequent molecules.…”
mentioning
confidence: 78%
“…4), a phenomenon most oen observed in equilibrium-based olen/paraffin separations. 28 Together, these data provide strong evidence that it is quite important in POP-based gas separation to have a proper size matching of the adsorbent pores to that of the adsorbate molecules. For the metallated materials reported herein, this size-matching mechanism can become important aer the rst olen binds to the metal center and reduces the accessibility of the metallated pores for subsequent molecules.…”
mentioning
confidence: 78%
“…MIL-100 (Fe) was synthesized with a modified method [46]. FeCl 3 ·6H 2 O (2.7 g), 1,3,5-benzenetricarboxylic acid (1.4 g) and 60 mL H 2 O were added to teflon-lined steel autoclaves and maintained at 150 °C for 12 h. After cooling, the light orange solid products were filtered and recovered by two-step method of hot water (80 °C) and ethanol (60 °C) for further purification.…”
Section: Methodsmentioning
confidence: 99%
“…FeCl 3 ·6H 2 O (2.7 g), 1,3,5-benzenetricarboxylic acid (1.4 g) and 60 mL H 2 O were added to teflon-lined steel autoclaves and maintained at 150 °C for 12 h. After cooling, the light orange solid products were filtered and recovered by two-step method of hot water (80 °C) and ethanol (60 °C) for further purification. After drying at 80 °C, MIL-100 (Fe) was dried at 150 °C overnight in a vacuum [46]. The synthetic details of MIL-100(Cr) [43] and MIL-101(Cr) [47] were shown in Supplementary Materials.…”
Section: Methodsmentioning
confidence: 99%
“…61 Finally, when Fe 3+ is involved in these mesoporous solids, we recently showed that their thermal activation under vacuum, not only creates CUS, but the disparition of the OH/F groups simultaneously induces a partial Fe 3+ -Fe 2+ reduction in the framework which enhances the propane-propylene separation at room temperature. 62…”
Section: Co 2 and Ch 4 Adsorption In Crystallized Mesoporous Solids M...mentioning
confidence: 99%